Establishing Community Of Practice In The University College Hospital, Ibadan, Nigeria - Ikeazota, Lilian Onyedikachi (European Scientific Journal, ESJ, 2016)
The aim of this paper is to discuss the need for a community of practice in the University College Hospital, Ibadan, Nigeria. The requirements for the community of practice involve the personnel, the facilities, and the process of establishing it in the institution. A well cultivated community of practice will exhibit the three elements of Wenger’s model. Also, it would provide results as regards to problem solving, shared knowledge, and experience. In the era of recession and budget cuts, there is the need for library services to be maintained at its best. Effective and efficient innovative ways are applied in maintaining the library and the services it offers to its users. Sponsors should support the take-off. In addition, such goodwill will receive reward in terms of commendation once the group commences.